Method for preparing multifunctional composite flocculant by utilizing pyrolysis carbonized slag
Through magnetic separation, catalytic activation and acid-soluble oxidation reaction, the pyrolytic carbonized slag is converted into a multifunctional composite flocculant, which solves the problem of high energy consumption in the prior art and difficult to directly recover and utilize the products, and achieves the effect of treating high COD and high color wastewater with low energy consumption.
Patent Information
- Application Number
- CN202411531618.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the prior art, when treating iron-rich oil-containing sludge pyrolyzed carbonized slag, energy-consuming and recovered crude iron products are difficult to directly utilize, and an additional refining process is required.
Through magnetic separation, catalytic activation and acid-soluble oxidation reaction, the pyrolytic carbonized slag is treated into a multifunctional composite flocculant, including activated carbon, ferric chloride and a small amount of magnesium, calcium, cobalt, manganese and zinc ions. This flocculant can be used for efficient adsorption and flocculation of COD and chromaticity in wastewater.
The pyrolytic carbonized slag is converted into a multifunctional composite flocculant with low energy consumption, which can be directly used to treat high COD and high color wastewater, and has the dual effects of adsorption and flocculation, which improves the treatment effect.
Smart Images

Figure BDA0005110602550000061 
Figure BDA0005110602550000071 
Figure BDA0005110602550000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste treatment, and more specifically, to a method for preparing a multifunctional composite flocculant by utilizing pyrolysis carbonized slag. Background Art
[0002] With the acceleration of the industrialization process, a large amount of industrial waste is generated in production activities such as mechanical processing, metal surface treatment, equipment maintenance and replacement, and disassembly. Among them, iron-rich oily sludge, a viscous semi-solid waste with a high degree of emulsification of water, oil, and slag, has attracted much attention because it contains high concentrations of toxic and harmful components such as petroleum hydrocarbons, polycyclic aromatic hydrocarbons (PAHs), heavy metals, bacteria, suspended solids, chemicals, and a large amount of aged crude oil and iron. Iron-rich oily sludge not only poses a serious threat to the environment, but is also a renewable resource with extremely high potential for resource utilization and industrial recycling value.
[0003] It is estimated that the annual output of iron-rich and oily sludge in my country is as high as 3 million tons. In view of its resource nature and harmfulness, efficient and clean treatment, disposal and resource utilization technology has become a research hotspot in the field of energy and environment. As an emerging treatment method, low-temperature anaerobic pyrolysis technology of oily sludge has the advantages of low process energy consumption, clean combustion, environmentally friendly emissions (no dioxin production), and heavy metal solidification. In an anaerobic closed system, iron-rich and oily sludge is indirectly heated and carbonized and decomposed into pyrolysis oil, pyrolysis carbon and pyrolysis gas. Pyrolysis gas can be used as fuel, pyrolysis oil can be used as raw material for fuel oil or organic raw material production, and pyrolysis carbon contains high carbon and magnetite (Fe3O4), which has recycling value.
[0004] However, magnetic separation technology is currently mainly used to recover iron and carbon resources from the carbonized slag of iron-rich and oily sludge. Since the distribution of carbon and iron elements in the carbonized slag is embedded, wrapped and interwoven, the effect of magnetic separation and recovery of iron and carbon resources is not ideal. The method for recovering metallic iron from pyrolytic carbon slag disclosed in the prior art uses a high-temperature carbon thermal reduction method to recover iron resources from the pyrolytic carbon slag, adding reducing carbon powder and slag-forming agents, but due to ultra-high temperature calcination, the energy consumption is relatively large, and the crude iron product obtained is difficult to be directly recycled and requires additional refining.
[0005] Therefore, it is of great research significance to develop a low-energy and high-efficiency method that can directly recycle the iron and carbon resources in pyrolysis carbonized slag. Summary of the invention
[0006] The invention aims to overcome the shortcomings of high energy consumption in treating pyrolytic carbonized slag and difficulty in recycling the product by conventional methods, and provides a method for preparing a multifunctional composite flocculant by using pyrolytic carbonized slag.
[0007] Therefore, the primary purpose of the present invention is to provide a method for preparing a multifunctional composite flocculant using pyrolytic carbonized slag.
[0008] Another object of the present invention is to provide a multifunctional composite flocculant prepared by the above preparation method.
[0009] Another object of the present invention is to provide an application of the multifunctional composite flocculant.
[0010] To achieve the above object, the present invention adopts the following technical solutions:
[0011] The present invention protects a method for preparing a multifunctional composite flocculant by using pyrolytic carbonized slag, which is characterized by comprising the following steps:
[0012] S1. Magnetic separation: pyrolysis carbonized slag is magnetically separated to remove non-magnetic impurities and obtain iron-carbon particles;
[0013] S2. Catalytic activation: adding an activator zinc chloride solution and a catalyst to the iron-carbon particles, reacting at 500°C to 900°C under an inert atmosphere for 3 to 7 hours to obtain iron-containing activated carbon;
[0014] S3. Acid oxidation: adding the iron-containing waste hydrochloric acid to the iron-containing activated carbon to react, and then adding an oxidant to react to obtain a multifunctional composite flocculant;
[0015] Wherein, the catalyst is one or more of magnesium oxide, calcium oxide, cobalt oxide or manganese dioxide;
[0016] The mass ratio of zinc chloride to pyrolysis carbonized slag in S2 is (0.3-0.5): (1-5);
[0017] The added mass of the catalyst in S2 is 0.1-2.0% of the mass content of the pyrolysis carbonized slag.
[0018] The present invention processes pyrolytic carbonized slag into a multifunctional composite flocculant liquid containing activated carbon, ferric chloride, a small amount of magnesium, calcium, cobalt, manganese and zinc ions through magnetic separation, catalytic activation and acid-dissolving oxidation reaction, and can remove COD and chroma in wastewater through efficient adsorption and flocculation.
[0019] Specifically, the present invention first obtains iron-carbon particles with non-magnetic impurities removed by magnetic separation, wherein the impurities include non-magnetic mineral particles, ash, unreacted raw materials, and other non-iron and non-carbon residues, which are derived from the original components of the iron-rich oily sludge, or are by-products generated by chemical reactions during the pyrolysis process.
[0020] Secondly, the iron-carbon particles are catalyzed and activated to obtain iron-containing activated carbon:
[0021] The catalyst used is one or more of magnesium oxide, calcium oxide, cobalt oxide or manganese dioxide. On the one hand, it plays a catalytic role in the activation process, increases the reaction rate in the activation process, reduces the reaction temperature and time of the activation, changes its chemical reaction mechanism, and makes the carbides that originally could not form pores undergo chemical reactions to form pores, thereby effectively increasing the specific surface area of the carbon matrix, improving the pore structure and enhancing the adsorption performance to prepare iron-containing activated carbon; on the other hand, in order to introduce a small amount of calcium, magnesium, and manganese ions into the flocculant prepared later, it can effectively promote the flocculation and precipitation of organic matter to the bottom of the water. Specifically, the ionized positive ions in the water (such as Ca 2+ Mg 2+ etc.) can neutralize or reduce the negative charge on the surface of the colloid, reduce the uncompensated bond energy, weaken the repulsion between them, destroy the stable state of the colloid, and make them collide and contact under the action of molecules, destabilize to form floccules, and then settle down. In short, the catalyst plays a catalytic role, has the dual role of coagulation and enhancing adsorption performance. A small amount of addition will significantly reduce the chromaticity and COD removal rate, but it should not be excessive, because the catalyst is mainly alkaline earth metal oxides, and excessive addition will cause the flocculant system to become unstable and deteriorate, which will affect the chromaticity and COD removal rate of the water quality.
[0022] The activator used is zinc chloride, which can activate the carbon matrix, make it have a larger microporous volume, increase the adsorption specific surface area and adsorption pores, adsorption points, and improve the yield and adsorption capacity of iron-containing activated carbon. In addition, zinc chloride has a catalytic dehydration effect at high temperature. It can dehydrate and condense with oxygen-containing functional groups to separate hydrogen and oxygen atoms in the raw materials in the form of water, forming a loose porous and water-permeable structure, that is, iron-containing activated carbon, and retain more carbon in the raw materials, thereby improving the yield and adsorption capacity of iron-containing activated carbon. In short, zinc chloride plays an activating role and can improve the carbon matrix yield and adsorption capacity of the flocculant. If the amount added is small, it is difficult to activate the reaction of the iron-carbon particles to the iron-containing activated carbon. If the amount added is large, the flocculation performance of the flocculant will be reduced (such as: affecting the adsorption and electrical neutralization ability of the flocculant, etc.), and the zinc content in the water will return to a high level and exceed the standard.
[0023] Finally, iron-containing waste hydrochloric acid and an oxidant are added to react with the obtained iron-containing activated carbon to prepare a multifunctional composite flocculant liquid. The iron in the iron-containing activated carbon is dissolved with waste hydrochloric acid to achieve separation of iron and carbon. On the one hand, the use of iron-containing waste hydrochloric acid can make use of the iron-containing waste acid after industrial pickling as a resource, and on the other hand, the iron ions in the iron-containing waste hydrochloric acid can supplement the source of iron, which is beneficial to increase the iron content in the composite flocculant. The oxidant converts the ferrous ions generated after the iron-containing waste hydrochloric acid dissolves the iron into trivalent ferrous ions. The multifunctional composite flocculant liquid finally obtained contains activated carbon, ferric chloride, a small amount of magnesium, calcium, cobalt, manganese and zinc ions, which can work together in the water treatment process of efficient adsorption and flocculation to remove COD and chroma in wastewater.
[0024] Preferably, the catalyst is magnesium oxide, calcium oxide, cobalt oxide and manganese dioxide. More preferably, the mass ratio of magnesium oxide, calcium oxide, cobalt oxide and manganese dioxide is 1:1:1:1.
[0025] Preferably, the magnetic strength of the magnetic separation in S1 is 100 to 500 Gs.
[0026] Specifically, the pyrolytic carbonized slag is obtained by indirect heating and carbonization decomposition of iron-rich oil-containing sludge in an anaerobic closed system, and contains relatively high carbon and magnetite (Fe3O4). Preferably, the mass content of carbon in the pyrolytic carbonized slag in S2 is 10-20%.
[0027] Preferably, the iron mass content of the pyrolytic carbide slag in S2 calculated as Fe3O4 is 20-30%.
[0028] Preferably, the mass ratio of the activator zinc chloride solution to the pyrolysis carbonized slag in S2 is 1:(1-5).
[0029] Preferably, the concentration of the activator zinc chloride solution in S2 is 3-5 mol / L.
[0030] Preferably, the inert gas in S2 is one or more of nitrogen, argon or helium.
[0031] Preferably, the gas flow rate of the inert gas in S2 is 2 to 4 m 3 / h.
[0032] Preferably, the mass content of hydrochloric acid in the iron-containing waste hydrochloric acid in S3 is 15-20%.
[0033] Preferably, the iron content of the iron-containing waste hydrochloric acid in S3 is 5% to 10%.
[0034] Preferably, the mass ratio of the iron-containing waste hydrochloric acid in S3 to the iron-containing activated carbon is (3-4):1.
[0035] Preferably, the oxidant in S3 is one or both of sodium chlorate and hydrogen peroxide.
[0036] More preferably, the oxidant in S3 is sodium chlorate.
[0037] Preferably, the amount of the oxidant added in S3 is 1.5% to 2.5% of the total mass of the iron-containing waste hydrochloric acid and the iron-containing activated carbon.
[0038] The invention protects a multifunctional composite flocculant, which is prepared by the above preparation method.
[0039] The present invention also protects the application of the multifunctional composite flocculant in water treatment.
[0040] Further preferably, the application of the multifunctional composite flocculant in treating high COD and high chroma wastewater is also within the protection scope of the present invention.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The present invention provides a method for preparing a multifunctional composite flocculant by using pyrolytic carbonized slag, wherein the pyrolytic carbonized slag is treated with mild catalytic activation to prepare iron-containing activated carbon, thereby avoiding the energy consumption caused by ultra-high temperature calcination treatment in the prior art;
[0043] 2. The method of preparing a multifunctional composite flocculant using pyrolytic carbonized slag of the present invention uses iron-carbon particles in the pyrolytic carbonized slag to prepare a multifunctional composite flocculant, which can be directly used to treat COD and chromaticity in wastewater;
[0044] 3. The present invention provides a multifunctional composite flocculant with dual functions of adsorption and flocculation, which is suitable for the treatment of high COD and high chroma wastewater. The COD removal and decolorization capabilities are superior to those of conventional ferric chloride water treatment agents, and the dosage is only 0.8‰, which is efficient and durable. DETAILED DESCRIPTION
[0045] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0046] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0047] 1. Experimental methods
[0048] Example 1 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0049] S1. Magnetic separation: Magnetic separation is used to remove impurities from the pyrolysis carbonized slag.
[0050] Specifically, the pyrolytic carbonized slag is passed through a magnetic separator to remove non-magnetic impurities in the slag, and the magnetic strength is 300 Gs to obtain iron-carbon particles.
[0051] S2. Catalytic activation: The pyrolytic carbonized slag is treated with an activator and a catalyst.
[0052] Specifically, the iron-carbon particles after impurity removal in S1 are ground through a 200-mesh sieve, and a 4 mol / L zinc chloride solution is added, the mass ratio of the zinc chloride solution to the pyrolysis carbonization slag is 0.4:3, and then magnesium oxide, calcium oxide, cobalt oxide and manganese dioxide catalysts of the mass of the pyrolysis carbonization slag are added, and the total amount added is 1.0% of the mass of the pyrolysis carbonization slag, wherein the mass ratio of magnesium oxide, calcium oxide, cobalt oxide and manganese dioxide is 1:1:1:1. After being mixed evenly, it is placed in a tubular furnace, nitrogen is introduced, and it is roasted at 600°C for 4 hours to obtain iron-containing activated carbon.
[0053] S3. Acid dissolution oxidation: Add waste hydrochloric acid and oxidant to prepare a multifunctional composite flocculant.
[0054] Specifically, the iron-containing activated carbon obtained in S2 is ground and passed through a 200-mesh sieve, and iron-containing waste hydrochloric acid is added at a mass ratio of 1:3.5, and stirred in a 70°C water bath for 1.5 hours to form a mixed solution, and then 2.0% of the total mass of the mixed solution as an oxidant, sodium chlorate, is added and oxidized for 10 minutes to obtain a multifunctional composite flocculant liquid.
[0055] Example 2 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0056] The solution is the same as that of Example 1, except that the mass ratio of zinc chloride added to pyrolysis carbonized slag is 0.4:1.
[0057] Example 3 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0058] The solution is the same as that of Example 1, except that the mass ratio of zinc chloride added to pyrolysis carbonized slag is 0.4:5.
[0059] Example 4 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0060] The solution is the same as that of Example 1, except that the temperature of catalytic activation is 500°C.
[0061] Example 5 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0062] The solution is the same as that of Example 1, except that the temperature of catalytic activation is 700°C.
[0063] Example 6 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0064] The solution is the same as that of Example 1, except that the temperature of catalytic activation is 900°C.
[0065] Example 7 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0066] The same scheme as in Example 1, except that the catalytic activation time is 3 h.
[0067] Example 8 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0068] The same scheme as in Example 1, except that the catalytic activation time is 5 h.
[0069] Example 9 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0070] The same scheme as in Example 1, except that the catalytic activation time is 7 h.
[0071] Example 10 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0072] The same scheme as in Example 1, except that the catalyst is magnesium oxide.
[0073] Example 11 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0074] The same scheme as in Example 1, except that the catalyst is calcium oxide.
[0075] Example 12 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0076] The same scheme as in Example 1, except that the catalyst is cobalt oxide.
[0077] Example 13 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0078] The same scheme as in Example 1, except that the catalyst is manganese oxide.
[0079] Example 14 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0080] The solution is the same as that of Example 1, except that the amount of catalyst added is 0.5% of the pyrolysis carbonized slag.
[0081] Example 15 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0082] The solution is the same as that of Example 1, except that the amount of catalyst added is 0.1% of the pyrolysis carbonized slag.
[0083] Example 16 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0084] The solution is the same as that of Example 1, except that the amount of catalyst added is 2.0% of the pyrolysis carbonized slag.
[0085] Comparative Example 1 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0086] The same scheme as in Example 1, except that the mass ratio of zinc chloride to pyrolytic carbonized slag is 0.4:0.5. Comparative Example 2 A method for preparing a multifunctional composite flocculant using pyrolytic carbonized slag
[0087] The solution is the same as that of Example 1, except that the mass ratio of the added zinc chloride to the pyrolytic carbonized slag is 0.4:6.
[0088] Comparative Example 3: A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0089] The same scheme as in Example 1, except that no zinc chloride solution is added.
[0090] Comparative Example 4: A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0091] The same scheme as in Example 1, except that no catalyst is added.
[0092] Comparative Example 5: A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0093] The solution is the same as that of Example 1, except that the amount of catalyst added is 3% of the pyrolysis carbonized slag.
[0094] Comparative Example 6: A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0095] The same scheme as in Example 1, except that the temperature of catalytic activation is 200°C.
[0096] Comparative Example 7 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0097] The solution is the same as that of Example 1, except that the temperature of catalytic activation is 1000°C.
[0098] Comparative Example 8: A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0099] The same scheme as in Example 1, except that the catalytic activation time is 1 h.
[0100] Comparative Example 9: A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0101] The same scheme as in Example 1, except that the catalytic activation time is 8 h.
[0102] Comparative Example 10 A method for preparing a multifunctional composite flocculant using pyrolysis carbonized slag
[0103] The solution is the same as that of Example 1, except that the reaction gas atmosphere for catalytic activation is oxygen.
[0104] 2. Experimental results of Examples 1 to 16 and Comparative Examples 1 to 10
[0105] (1) Product performance index evaluation
[0106] The effective indicators of the multifunctional composite flocculant liquid prepared in the above examples and comparative examples were comprehensively evaluated. The evaluation standards and detection methods were referred to "GB / T 4482-2018 Water Treatment Agent Ferric Chloride". The specific detection results are shown in Table 1:
[0107] Table 1 Main performance indicators of multifunctional composite flocculant products
[0108]
[0109]
[0110] (2) Evaluation of chemical wastewater treatment effects
[0111] The chemical wastewater produced by a chemical plant was used as simulated wastewater, and its water quality is shown in Table 2. Using the control variable method, under the same experimental conditions, the multifunctional composite flocculants prepared in the above embodiments and comparative examples were added to 200 ml of chemical wastewater at a dosage ratio of 0.8‰, stirred at the same speed for 5 to 10 minutes, and the supernatant was taken to detect COD and chromaticity after standing for 30 minutes. The sewage treatment effects of the multifunctional composite flocculants prepared in the embodiments and comparative examples and the conventional ferric chloride water treatment agent were compared and explored, and the results are shown in Table 3.
[0112] Table 2 Chemical wastewater quality indicators
[0113]
[0114]
[0115] Table 3 Sewage treatment effect of the embodiment and the comparative example (the dosage of the agent is 0.8‰)
[0116]
[0117]
[0118] As can be seen from Table 1, the iron content, HCl content and carbon matrix content of the multifunctional composite flocculant prepared by the present invention meet the standard requirements of "GB / T 4482-2018 Water Treatment Agent Ferric Chloride" and can be directly used in water treatment.
[0119] As shown in Table 3, the COD and chromaticity removal rates of the flocculants obtained in Examples 1 to 16 are higher than the treatment effect of the conventional ferric chloride water treatment agent, and are applied to wastewater with high COD concentration and high chromaticity; Comparative Examples 1 to 3 illustrate the importance of the activator zinc chloride, which will increase the yield of iron-containing activated carbon, enhance the adsorption effect, and improve the removal effect of chromaticity. It can be seen from the data of Comparative Example 3 that when zinc chloride is not added, although the carbon matrix content left is relatively high, it is basically inert carbon and is not activated, and there are no available pores and active sites for adsorption and flocculation, so the removal effect is poor, but too much zinc chloride will reduce the flocculation effect; Comparative Examples 4 to 6 illustrate the importance of the catalyst, which enhances the adsorption and coagulant effect of the flocculant, that is, removes chromaticity and COD. A small amount of addition will reduce the removal rate of chromaticity and COD. The addition of the catalyst should not be excessive, because the catalyst is mainly alkaline earth metal oxide, and excessive addition will cause the flocculant system to become unstable and deteriorate. On the contrary, it will affect the chromaticity of water quality and COD removal rate; Comparative Examples 6 to 7 illustrate the temperature and time ranges in different conditions and treatment methods. The reaction temperature of the catalytic activation in Comparative Example 6 is too low to fully form pores in the iron-carbon particles, and the active sites required for subsequent adsorption are also insufficient, so the removal effect is not good; the temperature in Comparative Example 7 is too high, collapse will occur, and the adsorption sites of iron-containing activated carbon will be reduced; the reaction time of the catalytic activation in Comparative Example 8 is too short, and it is difficult for the activator and catalyst to fully react with the iron-carbon particles, and the degree of pore formation of the iron-containing activated carbon is also insufficient; the catalytic activation time in Comparative Example 9 is too long, and excessive catalytic activation may lead to a decrease in the yield of activated carbon, and long-term high temperature may cause more carbon to be oxidized, thereby reducing the output of activated carbon; Comparative Example 10 uses an oxygen atmosphere. Under high temperature conditions, the reactants are easily oxidized with oxygen in the air, resulting in oxidation of the iron-carbon particles, reducing the carbon content, and reducing the adsorption and flocculation effects, and there is a safety risk of explosion.
[0120] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a multifunctional composite flocculant using pyrolytic carbonized slag, characterized in that: The following steps are involved: S1. Magnetic separation: pyrolysis carbonized slag is magnetically separated to remove non-magnetic impurities and obtain iron-carbon particles; S2. Catalytic activation: adding an activator zinc chloride solution and a catalyst to the iron-carbon particles, reacting at 500°C to 900°C under an inert atmosphere for 3 to 7 hours to obtain iron-containing activated carbon; S3 acid oxidation: adding the iron-containing waste hydrochloric acid to the iron-containing activated carbon in S2, and then adding an oxidant to react to obtain a multifunctional composite flocculant; Wherein, the catalyst is one or more of magnesium oxide, calcium oxide, cobalt oxide or manganese dioxide; The mass ratio of zinc chloride to pyrolysis carbonized slag in S2 is (0.3-0.5): (1-5); The added mass of the catalyst in S2 is 0.1-2.0% of the mass content of the pyrolysis carbonized slag.
2. The method according to claim 1, characterized in that The magnetic strength of the magnetic separation in step S1 is 100 to 500 Gs.
3. The method according to claim 1, characterized in that The concentration of the activator zinc chloride solution in step S2 is 3-5 mol / L.
4. The method according to claim 1, characterized in that: In step S2, the inert gas is one or more of nitrogen, argon or helium.
5. The method according to claim 1, characterized in that: In step S3, the oxidant is one or both of sodium chlorate and hydrogen peroxide.
6. The method according to claim 1, characterized in that The amount of the oxidant added in step S3 is 1.5% to 2.5% of the total mass of the iron-containing waste hydrochloric acid and the iron-containing activated carbon.
7. The method according to claim 1, characterized in that The hydrochloric acid mass content of the iron-containing waste hydrochloric acid in step S3 is 15-20%.
8. The method according to claim 1, characterized in that: The iron content of the iron-containing waste hydrochloric acid in step S3 is 5% to 10%.
9. A multifunctional composite flocculant, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. Use of the multifunctional composite flocculant according to claim 9 in water treatment.
Citation Information
Patent Citations
Method for manufacturing magnetic sludge-based active carbon
CN103406094A
Rare metal-based sludge activated carbon and application thereof in removal of sulfur, ammonia and phosphorus
CN106345411A
Decolorizing material, preparation method and application thereof and wastewater decolorizing method
CN110115974A
Porous carbon loaded metal oxide adsorbent as well as preparation method and application thereof
CN115722188A
Method for recovering metallic iron in pyrolytic carbon residues
CN116408338A